European Consensus Guidelines on the Management of Respiratory Distress Syndrome-2019 Update - ÖZEK, EREN (KARGER, 2019)
As management of respiratory distress syndrome (RDS) advances, clinicians must continually revise their current practice. We report the fourth update of European Guidelines for the Management of RDS by a European panel of experienced neonatologists and an expert perinatal obstetrician based on available literature up to the end of 2018. Optimising outcome for babies with RDS includes prediction of risk of preterm delivery, need for appropriate maternal transfer to a perinatal centre and timely use of antenatal steroids. Delivery room management has become more evidence-based, and protocols for lung protection including initiation of CPAP and titration of oxygen should be implemented immediately after birth. Surfactant replacement therapy is a crucial part of management of RDS, and newer protocols for its use recommend early administration and avoidance of mechanical ventilation. Methods of maintaining babies on non-invasive respiratory support have been further developed and may cause less distress and reduce chronic lung disease. As technology for delivering mechanical ventilation improves, the risk of causing lung injury should decrease, although minimising time spent on mechanical ventilation using caffeine and, if necessary, postnatal steroids are also important considerations. Protocols for optimising general care of infants with RDS are also essential with good temperature control, careful fluid and nutritional management, maintenance of perfusion and judicious use of antibiotics all being important determinants of best outcome. (c) 2019 S. Karger AG, Basel
Keywords: Antenatal steroids; Continuous positive airway pressure; Evidence-based practice; Hyaline membrane disease; Mechanical ventilation; Nutrition; Oxygen supplementation; Patent ductus arteriosus; Preterm infant; Respiratory distress syndrome; Surfactant therapy; Thermoregulation; POSITIVE AIRWAY PRESSURE; EXTREMELY PRETERM INFANTS; BIRTH-WEIGHT INFANTS; HIGH-FLOW THERAPY; OXYGEN-SATURATION TARGETS; PATENT DUCTUS-ARTERIOSUS; LARYNGEAL MASK AIRWAY; BRONCHOPULMONARY DYSPLASIA; PREMATURE-INFANTS; RANDOMIZED-TRIAL